2005
DOI: 10.1021/jm050499d
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Cell-Permeable Non-Peptide Inhibitors of β-Secretase by High-Throughput Docking and Continuum Electrostatics Calculations

Abstract: A fragment-based docking procedure followed by substructure search were used to identify active-site beta-secretase inhibitors from a composite set of about 300 000 and a library of nearly 180 000 small molecules, respectively. EC(50) values less than 10 microM were measured in at least one of two different mammalian cell-based assays for 12 of the 72 purchased compounds. In particular, the phenylureathiadiazole 2 and the diphenylurea derivative 3 are promising lead compounds for beta-secretase inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 30 publications
(70 reference statements)
2
67
0
Order By: Relevance
“…Conversely, we did not target the active site, and the molecules selected by docking were devoid of chemically active warheads. The finding of only one active compound out of 29 substances is in line with previous studies, which showed that candidate inhibitors predicted by docking algorithms are not necessarily active in vitro (Huang et al 2005).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Conversely, we did not target the active site, and the molecules selected by docking were devoid of chemically active warheads. The finding of only one active compound out of 29 substances is in line with previous studies, which showed that candidate inhibitors predicted by docking algorithms are not necessarily active in vitro (Huang et al 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Molecules with more than nine rotatable bonds were neglected. The resulting 48,026 cluster representatives were docked as in previous in silico campaigns (Huang et al 2005(Huang et al , 2006Kolb et al 2008). For each molecule docked by the program FFLD (Fragment-based Flexible Ligand Docking) (Budin et al 2001;Cecchini et al 2004), the 300 most favorable poses were clustered with the leader algorithm yielding 764,776 poses (;17 poses per compound, 44,527 compounds).…”
Section: Dockingmentioning
confidence: 99%
“…12 On the contrary to free piperidine compounds 8 and 9, ureidopiperidine 11 with arylpiperazine at 3-position showed more potent activity than regioisomeric ureidopiperidine 10. Among the ureidopiperidine tested, 3,5-dichloro substituent resulted better activity than other substituents (11d-f).…”
Section: Resultsmentioning
confidence: 95%
“…A similar in silico fragment-based approach had been used previously to identify novel inhibitors of the aspartic protease β-secretase [10,11], two kinases [12,13], and a flaviviral serine protease [14]. The major difference between our previous in silico screening campaigns and the one reported here is the final scoring of the poses.…”
Section: Introductionmentioning
confidence: 99%